Fatal human herpes virus 6B myocarditis: Postmortem diagnosis of HHV-6B based on CD134+ T-cell tropism. (February 2022) - Yamada, Atsushi; Takeichi, Toshiaki; Kiryu, Kyoka; Takashino, Satoshi; Yoshida, Masaki; Kitamura, Osamu
Highlights: Precise diagnosis of HHV-6 myocarditis is crucial in forensics. We report a fatal case of HHV-6B myocarditis, diagnosed by a specific cell tropism. HHV-6B cell tropism via CD134, could be observed by immunofluorescence assay. Our report serves as postmortem diagnostic criterion for acute HHV-6 infection. Abstract: Human herpes virus 6 (HHV-6) is one of the most important pathogens of viral myocarditis, and is often responsible for sudden death in young adults. A 59-year-old immunocompetent man died of serious lymphocytic myocarditis, and his peripheral blood sample showed HHV-6 DNAemia. Recently, HHV-6 cell entry and reactivation have been suggested to be regulated by the expression of specific CD receptors on T lymphocytes. Here, we report a case of HHV-6 myocarditis diagnosed using an experimental method focused on this unique cell tropism. The interaction between HHV-6 and CD expression was assessed using an immunofluorescence assay. Colocalization between HHV-6B and CD134 was detected in lymphocytes infiltrating the myocardium, which was highly suggestive of an active HHV-6B infection and could be a useful criterion for postmortem diagnosis of HHV-6B myocarditis in the acute phase.